Understanding soil greenhouse gas fluxes in intensive maize-based cropping systems - Adviento-Borbe, Arlene; Achim Dobermann (Ann Arbor, MI ProQuest Dissertations & Theses Global, 2005)
"A field and three laboratory experiments were conducted to measure emissions of greenhouse gases in intensive irrigated maize-based systems managed at high yield levels with a view to understand how soil greenhouse gas productions are influenced by biogeochemical processes and crop management practices. Emissions ranged from 0.23 to 116 g N2O-N ha_1 d_1 and 0.18 to 54.8 kg CO2-C h_1 d_1 for recommended cropping systems (CCP1M1 and CSP1M1) and 0.93 to 162.8 g N2O-N ha_1 d_1 and 1.03 to 52.3 kg CO2-C ha_1 d_1 for intensive cropping systems (CCP3M2 and CSP3M2). Average annual N2O emission estimate in intensively managed CC and CS rotations was 7.5 kg N2O-N ha_1 yr_1 while average annual estimate in the recommended cropping systems (CCP1M1 and CSP1M1) was 5.5 kg N2O-N ha _1 yr_1. Seasonal N2O emission peaks were associated with high soil NO3 content, EC, soil/air temperature and water content. Average annual CO2 emission estimates in both levels of cropping management were 5.3 Mg CO2-C ha _1 yr_1 for CS rotation and 6.8 Mg CO 2-C ha_1 yr_1 for CC rotation suggesting that the CO2 emissions were significantly influenced by the amount and kind of crop residue returned to the field from the previous crop. The close relationship between soil electrical conductivity and N 2O and CO2 emissions in the field was further studied in the laboratory soil cores from six soil series (Kennebec, Floyd-Webster, Cecil, Sharpsburg, Yolo, and Valentine soils) at 0.5, 1.0, 1.5, 2.0 dS m _1 soil EC and 60% and 90% WFPS. In general, increasing soil EC values from 0.52 dS m_1 to 2.02 dS m_1 decreased the production of N2O via nitrification at 60 WFPS. However, at 90% WFPS, rates of N2O production were directly related to soil EC values. Possible reasons for such an inverse relationship include: a change in the activities/functions of microbial communities, decrease of bioavailable C and N following salt addition and the ability of bacterial cells to tolerate water and salt stress conditions. Based on the laboratory study of field soils, there was a 26% reduction of N2O emissions when a slow-release form of N fertilizer (ESN) was applied in the soil rather than NH4NO3. (Abstract shortened by UMI.)"--Abstract.
Thesis (PhD)--University of Nebraska--Lincoln, 2005
Includes bibliographical references
Keywords: Electronic books; Cropping systems; Greenhouse gases -- Environmental aspects